The rs5743836 polymorphism in TLR9 confers a population-based increased risk of non-Hodgkin lymphoma - Carvalho, A (2013)
Non-Hodgkin lymphoma (NHL) has been associated with immunological defects, chronic inflammatory and autoimmune conditions. Given the link between immune dysfunction and NHL, genetic variants in toll-like receptors (TLRs) have been regarded as potential predictive factors of susceptibility to NHL. Adequate anti-tumoral responses are known to depend on TLR9 function, such that the use of its synthetic ligand is being targeted as a therapeutic strategy. We investigated the association between the functional rs5743836 polymorphism in the TLR9 promoter and risk for B-cell NHL and its major subtypes in three independent case-control association studies from Portugal (1160 controls, 797 patients), Italy (468 controls, 494 patients) and the US (972 controls, 868 patients). We found that the rs5743836 polymorphism was significantly overtransmitted in both Portuguese (odds ratio (OR), 1.85; P=7.3E-9) and Italian (OR, 1.84; P=6.0E-5) and not in the US cohort of NHL patients. Moreover, the increased transcriptional activity of TLR9 in mononuclear cells from patients harboring rs5743836 further supports a functional effect of this polymorphism on NHL susceptibility in a population-dependent manner.